A Community Hospital's Evaluation of Alarm Management Safety Factors. (December 2016) - Kurnat-Thoma, Emma; Shah, Kayuri
Abstract : BACKGROUND: The Joint Commission's 2014 National Patient Safety Goals required hospitals to evaluate alarm safety in 2014–2015 and implement alarm safety policies. OBJECTIVE: The aim of this study was to assess common alarm management safety factors in our 187-bed community hospital. METHODS: Two weeks' worth of IV pump report data was evaluated to characterize 33 IV pump alarm types. Hospital and IV pump noise was measured, and an alarm management nurse survey was conducted. RESULTS: There were 8731 total IV pump alarms/alerts (24-hour mean, 623.6) across 6 units. The 2-minute idle alarm accounted for 32.4% of all total IV alarms/alerts, suggestive of high levels of nurse multitasking and nurse work interruptions. IV pump volumes contributed to overall hospital noise. Survey data identified patient units and alarm safety practices needing additional support. CONCLUSIONS: Characterization of IV pump alarms/alerts is an emerging area of scientific inquiry. Findings indicate the need for organizations to evaluate alarm burden and alarm management safety practices to reduce alarm fatigue risks.